Penerapan Kinerja Lingkungan terhadap Kinerja Perusahaan di PT XYZ Tbk. - Hendryan Nur Pratama; Epi Fitriah (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Company performance is an analysis to determine how well a company adheres to established rules for prudent financial management. It is measured by the level of profitability, using the Return on Assets (ROA) indicator. Environmental performance refers to a company's efforts in creating a favorable environment, measured by the Environmental Management Performance Rating Program (PROPER). This research aims to explain the implementation of environmental performance at PT XYZ Tbk., describe its overall performance, and elucidate how environmental performance can enhance the company's performance. Data was collected using literature review and descriptive data analysis methods, covering the period from 2019 to 2022. The study found that PT XYZ's environmental performance received a